Comparison Of The Number Of Salivary Bacterial Colonies In Caries And Non-Caries Children After Consuming Isotonic Drinks - Yaya Widyatmoko; Neny Setyawati Ningsih; Amakhul Husna (Jurnal Kesehatan Gigi, 2022)
ABSTRACTLevel of oral health very affected by level of bacteria colonies in saliva. One of oral disease which can happen because of development of caries is tooth caries. Isotonic drinks (soft drink) and other soft drink  have an a effect of oral health. Carbonated drink (soft drink), lactate, and isotonic drinks have same level of acidity. Point of this research is to know how different number of saliva bacteria colonies of children who had an caries and children who don`t have an caries after cosuming isotonic drinks.This research is the pseudo eksperiment research (quasi experiment). Design of this research is Pre and Post test with Control Group Design. Subject taken from student at the V class Elementary School 41 North Pontianak that is children who had an caries and non caries and subject this research taken by some criteria. The process of take saliva doing before and after consuming isotonic drink from 20 sample consists of 10 caries and 10 non caries and than breeding to be 40 colonies saliva bacteria in Microbiology Laboratory Health Polytechnic Kemenkes Pontianak. Static analysis do with used t-test.Number of colonies saliva bacteria of children who had an caries and non caries after consume isotonic drink obtained p value 0,05 is meaning have a significant different between two group. This mean comparison number of colonies saliva bacteria of children who had an a caries and non caries between before and after comsume isotonic drink in caries group as much 155,30 cfu and after treatment as much 232,20 cfu. Whie in non caries group before treatment as much 47,50 cfu and after treatment 101,50 cfu. This increase is much better than caries group as much 76,9 cfu while on non caries group as much 54 cfu.Based of the treatment result obtained is have an meaningfull different number colonies saliva bacteria of children who had an caries and non caries after consume isotonic drinkKeyword :Bacteria colonies, isotonic drink and caries